2022
DOI: 10.1016/s2589-7500(21)00250-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal SARS-CoV-2 infection timing on birth outcomes: a retrospective multicentre cohort study

Abstract: BackgroundThe impact of maternal SARS-CoV-2 infection remains unclear. In this study, we evaluated the risk of maternal SARS-CoV-2 infection on birth outcomes and how this is modulated by the pregnancy trimester in which the infection occurs. We also developed models to predict gestational age at delivery for people following a SARS-CoV-2 infection during pregnancy. MethodsWe did a retrospective cohort study of the impact of maternal SARS-CoV-2 infection on birth outcomes. We used clinical data from Providence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 31 publications
(39 reference statements)
5
101
1
3
Order By: Relevance
“…Preliminary surveillance results indicated that the Omicron VOC has a secondary attack rate of 10-13% and therefore factors that increase transmission, such as multi-occupancy housing and public-facing occupations, are important also for this variant. [22][23][24] Since socioeconomic deprivation is also a known independent risk factor for adverse pregnancy outcome, this could be a source of residual confounding in this study.…”
Section: Interpretation and Comparison With Related Studiesmentioning
confidence: 99%
“…Preliminary surveillance results indicated that the Omicron VOC has a secondary attack rate of 10-13% and therefore factors that increase transmission, such as multi-occupancy housing and public-facing occupations, are important also for this variant. [22][23][24] Since socioeconomic deprivation is also a known independent risk factor for adverse pregnancy outcome, this could be a source of residual confounding in this study.…”
Section: Interpretation and Comparison With Related Studiesmentioning
confidence: 99%
“…A retrospective multicenter study in United States concluded that acute COVID-19 severity was not correlated with gestational age at delivery whereas separate cohort study in United States reported significant increase in preterm delivery among critical group compared to severe group. [22, 26] Our study reported preterm delivery rate of 40.7% among pregnant women needing ICU/ ECMO/ ventilated/ death whereas Pierce-Williams reported preterm delivery rate of 27% among severe group and 88% among critical group. [22]…”
Section: Discussionmentioning
confidence: 80%
“…The ongoing war and humanitarian crisis in Ukraine has affected the care of patients and the efficiency of healthcare systems in the area, including both Eastern and non-Eastern European countries. Given these scenarios, it becomes especially important to analyze available clinical data to aid in TB prognosis and guide optimal treatment decisions for each patient (Falzon et al, 2018;Gröschel et al, 2018;Lange et al, 2020;Lino Ferreira da Silva Barros et al, 2021;Olaru et al, 2016) The increasing availability of patient EHR comprising multi-modal data can enable precision and personalized medicine initiatives to better understand TB and other diseases (Piekos et al, 2022). We analyzed EHR data from over 5000 patients across 10 countries from the NIH NIAID TB portals.…”
Section: Discussionmentioning
confidence: 99%